2016
DOI: 10.1021/acsnano.5b08145
|View full text |Cite
|
Sign up to set email alerts
|

Near Infrared-Guided Smart Nanocarriers for MicroRNA-Controlled Release of Doxorubicin/siRNA with Intracellular ATP as Fuel

Abstract: In chemotherapy, it is a great challenge to recruit endogenous stimuli instead of external intervention for targeted delivery and controlled release; microRNAs are the most promising candidates due to their vital role during tumorigenesis and significant expression difference. Herein, to amplify the low abundant microRNAs in live cells, we designed a stimuli-responsive DNA Y-motif for codelivery of siRNA and Dox, in which the cargo release was achieved via enzyme-free cascade amplification with endogenous micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
134
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(136 citation statements)
references
References 50 publications
1
134
0
1
Order By: Relevance
“…In our humble opinion, the increased metabolic resistance seen in 293T from Day 3 to Day 5 could be attributed to enhanced ceramide production and over-expression of glucosylceramide genes (GCS). It might also be theorized that DXR increased ceramide production by activating sphingomyelinase 34. Taken together, these two processes were suspected to induce a positive feedback cycle through Sp1, generating an anti-apoptotic force.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our humble opinion, the increased metabolic resistance seen in 293T from Day 3 to Day 5 could be attributed to enhanced ceramide production and over-expression of glucosylceramide genes (GCS). It might also be theorized that DXR increased ceramide production by activating sphingomyelinase 34. Taken together, these two processes were suspected to induce a positive feedback cycle through Sp1, generating an anti-apoptotic force.…”
Section: Resultsmentioning
confidence: 99%
“…DXR could also induce H 2 O 2 formation by an iron-mediated reaction, catalyzed by ferredoxin reductase 33. A report from Zhang et al showed that the penetration depth of DXR in vivo and in vitro was dependent on the composition and function of the ECM within a given tumor or spheroid 34. Understanding these properties would be essential in the development of efficient non-toxic anti-cancer vehicles.…”
Section: Introductionmentioning
confidence: 99%
“…This allows the drug to target only specific cells and thus maintain a concentration above the therapeutic concentration for a particular length of time. The main and popular stimuli for remotely triggered systems are near infrared (NIR) light, ultrasound and alternating magnetic field (AMF) [12]. NIR light can be used to stimulate plasmonic metallic nanoparticles (i.e., gold nanoparticles [GNPs]).…”
Section: Stimulus-responsive Nanocarriersmentioning
confidence: 99%
“…66 Tumor phototargeting has been achieved in vivo with a gold nanostructure under irradiation with a NIR laser. 52 …”
Section: Clinical Rationales and Consequencesmentioning
confidence: 99%